MRI Brain Findings in 126 Patients with COVID-19: Initial Observations from a Descriptive Literature Review - Edwin Gulko; M.L. Oleksk; William A. Gomes; Sana Ali; Hasit Mehta; Philip Overby; Fawaz Al‐Mufti; A. Rozenshtein (2020)
BACKGROUND AND PURPOSE: Recently, numerous investigational studies, case series, and case reports have been published describing various MR imaging brain findings in patients with COVID-19. The purpose of this literature review was to compile and analyze brain MR imaging findings in patients with COVID-19-related illness. MATERIALS AND METHODS: Literature searches of PubMed, publicly available Internet search engines, and medical journal Web sites were performed to identify articles published before May 30, 2020 that described MR imaging brain findings in patients with COVID-19. RESULTS: Twenty-two articles were included in the analysis: 5 investigational studies, 6 case series, and 11 case reports, encompassing MR imaging of the brain in 126 patients. The articles originated from 7 different countries and were published in 14 medical journals. MR imaging brain findings included specific diagnoses (such as acute infarct, posterior reversible encephalopathy syndrome) or specific imaging features (such as cortical FLAIR signal abnormality, microhemorrhages). CONCLUSIONS: The most frequent diagnoses made on brain MR imaging in patients with COVID-19 were acute and subacute infarcts. Other common findings included a constellation of leukoencephalopathy and microhemorrhages, leptomeningeal contrast enhancement, and cortical FLAIR signal abnormality.